La seguridad jurídica en las transacciones de bienes inmuebles en el sistema jurídico ecuatoriano - Vázquez Barros, Miriam Cecilia (2026)
Every day, challenges and difficulties arise in notarial activity involving decisions that can even be punitive for the practicing notary. A challenge is legal security in real estate transactions due to various situations that can represent a risk for the notarial process. However, there is no extensive bibliography on the topic. The objective of this study was to analyze the legal and juridical mechanisms that guarantee legal security in real estate transactions in Ecuador, with a particular focus on the roles of Notarial Law and the Property Registry. A bibliographic analysis was conducted with a qualitative approach and non- experimental design based on the documentary analysis of current regulations and literature. Notarial activity is based on principles such as public faith, truthfulness, and legality, which play a fundamental role in preventing conflicts and granting certainty through the public deed. Nevertheless, weaknesses were identified, especially in promises of sale, where the lack of mandatory verification of the legal status of the property generates risks. It is concluded that, although the Notarial Law and the Registry Law contribute to legal security, there are shortcomings in the Registry Law regarding review processes and data confrontation that can lead to misinterpretation at times. Therefore, it is necessary to strengthen verification mechanisms in pre-contractual stages to prevent fraud and guarantee the protection of the parties rights.